2023
DOI: 10.5005/jp-journals-10078-1386
|View full text |Cite
|
Sign up to set email alerts
|

Use of Latanoprostene Bunod as Adjunctive Glaucoma Therapy in Refractory Glaucoma

Abstract: A bstract Aim To investigate the long-term efficacy of adjunctive use of latanoprostene bunod (LBN), a new nitric oxide donating prostaglandin medication, in refractory cases of glaucoma at a tertiary care center. Materials and methods A review for patients who received add-on LBN was conducted from 1 st January 2018 to 31 st August 2020. A total of 33 patients (53 eyes) met the inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[17][18][19] In fact, while the responder analysis in the prior study of late-stage patients showed substantial proportions of patients achieved IOP lowering of ≥2, ≥3, and ≥4 mm Hg (60%, 46%, and 34%, respectively), 13 the responder analysis in the current study of patients with mild-to-moderate OAG/OHT showed that even higher proportions of patients achieved these levels of IOP lowering (≥80%, ≥75%, and ≥65%, respectively, at both post-index visits) in the overall dataset as well as in the subgroups who were switched from a prior PGA. Also of interest, in a retrospective analysis examining adjunctive use of LBN in patients with refractory glaucoma who were using 3 or more topical agents, addition of LBN produced an IOP reduction of 9% at 3 months, 14 whereas in a retrospective chart review of LBN in treatment-naïve patients (mean baseline IOP, 21.7 mm Hg in study eyes), LBN produced mean IOP decreases of ~31% from baseline to each follow-up visit. 19 Collectively, these realworld analyses demonstrate that LBN effectively lowers IOP across a wide range of OAG disease severities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] In fact, while the responder analysis in the prior study of late-stage patients showed substantial proportions of patients achieved IOP lowering of ≥2, ≥3, and ≥4 mm Hg (60%, 46%, and 34%, respectively), 13 the responder analysis in the current study of patients with mild-to-moderate OAG/OHT showed that even higher proportions of patients achieved these levels of IOP lowering (≥80%, ≥75%, and ≥65%, respectively, at both post-index visits) in the overall dataset as well as in the subgroups who were switched from a prior PGA. Also of interest, in a retrospective analysis examining adjunctive use of LBN in patients with refractory glaucoma who were using 3 or more topical agents, addition of LBN produced an IOP reduction of 9% at 3 months, 14 whereas in a retrospective chart review of LBN in treatment-naïve patients (mean baseline IOP, 21.7 mm Hg in study eyes), LBN produced mean IOP decreases of ~31% from baseline to each follow-up visit. 19 Collectively, these realworld analyses demonstrate that LBN effectively lowers IOP across a wide range of OAG disease severities.…”
Section: Discussionmentioning
confidence: 99%
“…Since receiving marketing approval, retrospective chart reviews of LBN have demonstrated additional IOP-lowering when LBN either replaced prior therapy in predominantly late-stage glaucoma patients or was used as an adjunctive therapy in patients predominantly on multiple medications. [13][14][15] The current study was specifically conducted to investigate the realworld efficacy (IOP-lowering) and safety of LBN in a representative sample of patients with mild-to-moderate OAG/ OHT who were on 1-2 topical IOP-lowering therapies and switched 1 or both of these existing treatments to LBN.…”
Section: Introductionmentioning
confidence: 99%